Menakar Literasi Mikrobiologi Mahasiswa Pendidikan Biologi Universitas Mataram - Sakaroni, Rubiyatna; Wirdullutfi, Wirdullutfi; Hijriani, Baiq Isti (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2025)
Microbiology literacy is an important skill for prospective biology teachers to be able to understand, teach, and apply microbiology concepts appropriately in life and learning. This study aims to describe the microbiology literacy profile of biology education students at Mataram University based on competency and attitude dimensions after completing microbiology courses. The study employs a quantitative descriptive approach using instruments developed based on the PISA 2015 science literacy framework. The research subjects were students who had taken microbiology courses. Data were analyzed descriptively to determine literacy score categories. The results showed that students' microbiology literacy was generally in the moderate to low category. In the competency dimension, the highest scores were in the ability to interpret data and scientific evidence, while the lowest scores were in the ability to evaluate and design scientific investigations. In the dimension of attitude, the majority of students were in the moderate category, with the highest scores in the assessment of scientific approaches and the lowest scores in interest in microbiology. These low scores indicate the need to strengthen higher-order thinking skills, hands-on experience in research design, and learning that links microbiology concepts to real-life contexts. This study recommends the use of project-based, problem-based, and socio-scientific issue-based learning strategies, as well as evaluations that require the application of concepts and analysis. This approach is expected to enhance students' conceptual understanding, analytical skills, and scientific attitudes in a balanced manner.